PEMBUATAN MEDIA PEMBELAJARAN TINGKAT DASAR (SD/MI/SDIT) DENGAN MEMANFAATKAN LIMBAH SAMPAH (KARDUS) UNTUK METERI SISTEM PENCERNAAN MANUSIA - Dwi Rosyidatul Kholidah; Choerul Anwar Badruttamam; Anis Ulfiyatin (Pusat Penelitian Pengabdian Pada Masyarakat Sekolah Tinggi Ilmu Tarbiyah Al-Fattah Siman Lamongan, 2021)
The use of media in the learning process can generate new desires and interests, generate motivation, and stimulate learning activities, and even bring psychological effects on students, especially early age students. The use of instructional media will help the effectiveness of the learning process and the delivery of messages and lesson content. Learning media is useful in clarifying the delivery of teaching material, overcoming space and time, spurring children to be more active, and can increase cooperation. The benefits of using a learning media will be felt optimally if the teacher is able to select and use the media in accordance with its goals and functions. Digestive process media made of cardboard that is no longer used is one of the many media that can be obtained from the surrounding environment which is useful for learning children at the SD / MI / SDIT level. Besides being useful for students, learning media is also useful for educators. Educators will also get skills to design instructional media designs, make them, and maintain learning media properly.